Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPA dengan Model Problem Based Learning di Kelas V SDN 09 Koto Luar Kota Padang - Refeniwati, Riza; Arlis, Syamsu; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This class action research aims to improve science learning outcomes by using the Problem Based Leraning model in class V SD 09 Koto Luar, Padang City. The research subjects were 24 students in class V. The results showed a) that the RPP in the first cycle obtained an average value of 80.35% (Good) in the second cycle to 96.42% (Very Good), b) the implementation of learning from the aspect of the teacher in the first cycle obtained a value of 76.78 % (Good) in the second cycle to 96.42% (Very Good), in terms of aspects of students in the first cycle scored 73.21% (enough) in the second cycle to 92.85% (Very Good), c) learning outcomes students in the first cycle scored 73.33 (enough) in the second cycle to 86.06 (Very Good). Thus, the Problem Based Learning Model can improve science learning outcomes in class V SD N 09 Koto Luar, Padang.